Accessory Branch of Median Nerve Supplying the Brachialis Muscle: A Case Report and Clinical Significance - George Paraskevas; Nikolaos Anastasopoulos; Zoi Nitsa; Panagiotis Kitsoulis; Ioannis Spyridakis (Journal of Clinical and Diagnostic Research, 2014)
A very rare case of an accessory branch of the median nerve taking its origin in the region of the right arm was observed to supply the infero-medial portion of the brachialis muscle in a male cadaver. Simultaneously, the ipsilateral musculocutaneous nerve was innervating the muscles of the anterior compartment of the arm. Such an aberrant muscular branch of the median nerve for the brachialis muscle is very rarely reported in the literature. Lesion of the median nerve proximal to the branch’s origin site could induce weak flexion of the elbow, whereas injury of the musculocutaneous nerve could lead to misinterpretation of symptoms. We discuss the patterns of brachialis muscle innervation as well as the clinical applications of such a variant.